As Inteligências múltiplas e o aprendizado de química numa escola de educação profissional: um estudo de caso. - Sousa, Herlen Rios de (2018)
A broad field of educational research currently deals with curricular development, formation of teachers and teaching techniques. However, in practice, there is stilll a shortage of methodologies that are capable to provide an effective learning in abstract situations that requires the capacity to interpret and solve theoretical and practical problems. In this context, a main part of the research was concerned about the existence of a correlation among learning difficulties in Chemistry-related subjects and the deficiencies in the fields of the spatial, linguistic and logical mathematical intelligences, having the theory of the multiple intelligences as a basis. The target audience was a group of 19 students in the second year of high school in a state school of professional education, located in Fortaleza. The research was a case study with qualitative and quantitative approaches. The initial data collection instruments consisted of a survey questionnaire regarding the difficulties found in the learning of general chemistry, and another one regarding the intelligences that are the most related to chemistry learning. According to the results obtained, there were created workshops that could be able to develop activities that stimulated the development of competencies related to the called rational intelligences and associated to chemistry contents in which the students reported more comprehension problems. The workshops resulted in the educational product, described as a guide to orient in detail the performance of activities, in order to be used by the interested ones in this teaching method.